2007
DOI: 10.1063/1.2739364
|View full text |Cite
|
Sign up to set email alerts
|

Improved efficiency of zinc phthalocyanine/C60 based photovoltaic cells via nanoscale interface modification

Abstract: The photovoltaic performance of zinc phthalocyanine (ZnPc)∕C60 heterojunctions is improved by alternately depositing ultrathin active layers between the two bulk layers. Using a proper multilayer structure, a 60% improvement in conversion efficiency under AM1.5 illumination is obtained, in comparison with that of flat heterojunctions. Transmission electron microscope investigations reveal an effective phase separation of ZnPc and C60 and a high degree of crystalline ordering of C60 in this system. The authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 12 publications
5
35
0
1
Order By: Relevance
“…We focus on multi-layered structures as these enable us to vary the interfacial volume while maintaining the superior mobility of neat films. Alternate deposition of ultrathin layers yields a phasesegregated morphology with superior charge transport vis-à-vis co-sublimed blends 22 .…”
Section: Resultsmentioning
confidence: 99%
“…We focus on multi-layered structures as these enable us to vary the interfacial volume while maintaining the superior mobility of neat films. Alternate deposition of ultrathin layers yields a phasesegregated morphology with superior charge transport vis-à-vis co-sublimed blends 22 .…”
Section: Resultsmentioning
confidence: 99%
“…In case of organic light emitting diodes, these advantages have resulted in first commercially available devices admitting the efficient conversion of electrical energy into light. [5][6][7][8][9][10] Among these concepts, photovoltaic elements based on exciton generation, diffusion to the donor-acceptor interfaces, and subsequent dissociation, are the most promising ones. 3,4 Therefore, various innovative device concepts implementing organic thin films are currently under investigation.…”
mentioning
confidence: 99%
“…It has been reported that the nano-scale multilayer heterojunction with ultrathin crystalline organic films can greatly improve photocurrent genration. 13,14 As one of the most promising OPV materials, metal phthalocynine including zinc phthalocyanine (ZnPc) is attracting continual interests due to its high absorption coefficient and good chemical and thermal stability. 15 The growth characteristics of evaporated phthalocynine films have been experimentally and theoretically investigated.…”
Section: Introductionmentioning
confidence: 99%